Computed Tomography of the Abdomen in Eight Clinically Normal Common Marmosets (Callithrix jacchus). (26th June 2017) - du Plessis, W. M.; Groenewald, H. B.; Elliott, D.
Summary: The aim of this study was to provide a detailed anatomical description of the abdomen in the clinically normal common marmoset by means of computed tomography (CT). Eight clinically healthy mature common marmosets ranging from 12 to 48 months and 235 to 365 g bodyweight were anesthetized and pre‐ and post‐contrast CT examinations were performed using different CT settings in dorsal recumbency. Abdominal organs were identified and visibility noted. Diagnostic quality abdominal images could be obtained of the common marmoset despite its small size using a dual‐slice CT scanner. Representative cross‐sectional images were chosen from different animals illustrating the abdominal CT anatomy of clinically normal common marmosets. Identification or delineation of abdominal organs greatly improved with i.v. contrast. A modified high‐frequency algorithm with edge enhancement added valuable information for identification of small structures such as the ureters. The Hounsfield unit (HU) of major abdominal organs differed from that of small animals (domestic dogs and cats). Due to their size and different anatomy, standard small animal CT protocols need to be critically assessed and adapted for exotics, such as the common marmoset. The established normal reference range of HU of major abdominal organs and adapted settings for a CT protocol will aid clinical assessment of the common marmoset.